Rancang Bangun Aplikasi Kasir - Alwi, Rangga; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The cashier is the person who receives and returns the remaining money to the customer. One of cashier's most important problems is the absence of modern tools, such as barcode scanners, which can simplify the cashier's performance in calculating the total amount of purchases by customers. That's why we need a cash register application with Android. The Waterfall method used by the author, because the process is carried out one by one, so that any errors can be resolved first before proceed to the next step. The application can scan more than one items simultaneously. Simultaneous scanning testing is performed with four items at once with different barcode sizes and is performed at different distances. The goal is to find out how far the application can capture the image of the barcode on the item. Keywords : Cashier, Android, Barcode